Spatial Analysis of Sustainable Land Use Development Coastal Areas in Batang Regency - Ahmad Ibnu Riza; Athoillah Islamy (Kementerian Perencanaan Pembangunan Nasional (Bappenas), 2020)
Batang Regency as the northern coastal area of Java islandexperiences a problem of land use management that has not been optimal so that there is a need for analysis of land use development in the coastal area of Batang Regency. The purpose of this study is to examine the direction of land use development in coastal areas of Batang Regency with spatial analysis. This research method implementsquantitative approach while the analytical techniqueis spatial analysis. Spatial analysis is performed to identify land use of thecoastal area in Batang Regency. The study scope of coastal areasis based on administrative subdistricts located along the coast of Batang Regency. This research utilizes Spot satellite image year 2015 with the map of regionalspatial pattern plan of Batang Regency in 20112031. The spatial analysis result of land use developmentinBatang Regency’s coastal area includes the suitable category of 18.130,65 (56,32%) while the unsuitable category is 14.059,44 (43,68%). Batang Sub-district’s suitable category is 1.214,03 ha, while the unsuitable category is 2.220,51 ha. Kandeman Sub-district’s suitable category is 1.565.02 ha, while the unsuitable category is 2.610,65 ha. TulisSub-district’ssuitablecategory is 2.452,98 ha, while the unsuitable category is 2.055,80 ha. Subah Sub-district’ssuitablecategory is 5.381,89 ha, while the unsuitable category is 2.970,28 ha. Banyuputih Sub-district’s suitable category is 2.314,61 ha, while the unsuitable category is 2.127,89 ha. Gringsing Subdistrict’s suitablecategory is 5.202,12 ha, while the unsuitable categoryis 2.074,31 ha.The conclusion of land use planning development for Batang and Kandeman Sub-districts is that there are still a lot of lands designated for residential development. Subah Sub-district is for fisheries development while Tulis, Banyuputih, and Gringsing Sub-districts are for industrial development.